2000
DOI: 10.1038/sj.ejhg.5200487
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for quality improvement in genetic testing for cystic fibrosis European Concerted Action on Cystic Fibrosis

Abstract: These recommendations for quality improvement of cystic fibrosis genetic diagnostic testing provide general guidelines for the molecular genetic testing of cystic fibrosis in patients/individuals. General strategies for testing as well as guidelines for laboratory procedures, internal and external quality assurance, and for reporting the results, including the requirements of minimal services in mutation testing, the nomenclature for describing mutations, procedures to control false-positive amplification reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
7

Year Published

2001
2001
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 6 publications
(7 reference statements)
1
30
0
7
Order By: Relevance
“…These error rates are similar to those reported by a similar external proficiency testing program in Europe. [5][6][7] Analytic sensitivity…”
Section: Resultsmentioning
confidence: 99%
“…These error rates are similar to those reported by a similar external proficiency testing program in Europe. [5][6][7] Analytic sensitivity…”
Section: Resultsmentioning
confidence: 99%
“…20 In many situations where prior probabilities are in clearly different ranges (for instance 1/25 of being a carrier and 24/25 of being non-carrier), risk calculations can be performed by using simplified formulae, 20 which consist in assimilating the overall probability of having a negative result (denominator of the above formula) to 1 (100%). The simplified formulae are easy to use and the error, compared with the mathematically more correct ones, is often very small.…”
Section: Pðcjno Mutþ¼mentioning
confidence: 99%
“…20 These recommendations have been widely implemented in the framework of national or regional networks of diagnostics laboratories. However, an update has become necessary since many more laboratories are now offering CFTR genetic testing; the number of and indications for referrals have increased, in particular in the area of male infertility; knowledge of CFTR molecular pathology has evolved; and laboratory practice has changed, notably in the methods used.…”
Section: Introductionmentioning
confidence: 99%
“…This possibility has suggested that all CBAVD individuals and their partners should undergo genetic testing of the most common CFTR mutations before ART. 16,17 However, the utility of screening the couples candidates for an ART procedure for problems not related to obstructive azoospermia in the male partner and without a family history of CF is still debated. 18 In this study we report the results of a multicentric molecular screening of the most common CFTR gene mutations in 1195 couples undergoing ART, due to different causes of infertility.…”
Section: Introductionmentioning
confidence: 99%